2006
DOI: 10.1111/j.1468-2982.2004.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Headache Frequency in Adolescence

Abstract: Only a few studies have been published of the outcome of adolescent headache (HA). The aim of this study was to examine the predictors of the outcome of headache frequency. A population-based sample of 13-year-olds with or without HA (N=228) was followed to the age of 16 years. HA was classified on the basis of a face-to-face interview and clinical examination. The outcomes of monthly HA (>1/month) and non-frequent HA (0-1/month) were studied. Frequent use of analgesics, female gender and multiple non-headache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 60 publications
4
26
3
Order By: Relevance
“…Congruent results were found in a small population‐based study of 288 students followed‐up from age 13 to 16 in Turku, Finland. In these children, the presence of comorbid non‐headache pain at baseline was a negative prognostic factor for headache remission 27 . A population‐based cohort of 1046 children aged 11 to 14 from 39 schools in the Northwest of England, initially free of low back pain, were followed‐up for 1 year 28 .…”
Section: Proportion Of Swedish Adolescents Reporting Frequent Pain (Omentioning
confidence: 99%
“…Congruent results were found in a small population‐based study of 288 students followed‐up from age 13 to 16 in Turku, Finland. In these children, the presence of comorbid non‐headache pain at baseline was a negative prognostic factor for headache remission 27 . A population‐based cohort of 1046 children aged 11 to 14 from 39 schools in the Northwest of England, initially free of low back pain, were followed‐up for 1 year 28 .…”
Section: Proportion Of Swedish Adolescents Reporting Frequent Pain (Omentioning
confidence: 99%
“…However, conclusions about predictors cannot be taken because these studies reported a variety of outcome variables such as headache severity or percentage improvement. In addition, knowledge on the predictors of our primary outcome, attack frequency, is scarce and mainly available from prospective epidemiological studies 13‐15 . These studies indicated that medication overuse, female gender, presence of other pain symptoms, and depression increased the probability of having frequent attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies investigated only correlations between these variables in a cross-sectional study design 30,31. Studies that employed a longitudinal design investigated potential predictors that were not the focus of the present study 32,33…”
Section: Discussionmentioning
confidence: 98%